Impact of overgrazing and climate change on the lake ecosystem in arid region - Tserendorj, Uranchimeg; Tuulaikhuu, Baigal-Amar; Chananbaatar, Ayunshsuren; Moonkhor, Khishigjargal; Sharavjamts, Oyuntuya; Purevee, Ariunsuren; Purev, Tumenbayar; Naranbat, Dambadarjaa; Danzan, Tuvshinbayar; Myangan, Orgilbold; et al. (Mongolian Journal of Agricultural Sciences, 2022)
Mongolia's geographical location, extreme climate, fragile ecosystems, agricultural dependence on climate requires adaptation to global climate change and smart usage of natural resources. The water level of most lakes in Mongolia had been steadily increasing from mid-1960s to 1995 and declining from 1996. The purpose of this study is to determine current condition by each ecosystem compartment in and around the Lake Duruutsagaan and to define cause of the lake shrinking and deterioration of ecosystem. The Lake Duruutsagaan ecosystem study was carried out in the following natural elements: climate, hydrology, hydrobiology, forest, soil, pasture, plant species composition, and animals. The lake surface area was slightly decreased by 24.21% from 10.02 km2 in 2003 to 7.59 km2 in 2017. The lake water is highly mineralized, probably due to increases of evaporation of water. Also elevated concentrations of some chemical elements are detected in the lake water, including Phosphorus (22.6 mg L-1) and Arsenic (198 mg L-1). The high concentration of these two elements shown different kind of pollution existed in the lake. Probably, arsenic content in lake water is related to the geological composition of surrounding area, but elevated concentration of P can be attributed to the nutrient pollution due to soil erosion in surrounding area of lake. Species diversity in this lake is limited and only a few species of crustaceans that can tolerate under high salinity and polluted condition are present. All of soil samples have a low content of clay particles (between 2.6-8.5%). According to the soil samples data, pasture land in study area is moderately 80.95%, strongly 7.04% deteriorated due to direct and indirect effects of overgrazing. Especially, natural regeneration is not observed in the forest area. According to the study results, current condition of Lake Duruutsagaan and its surrounding area is indicating the need for some protection and restoration management.